A secondary analysis of the library profession's self-reported competence and comfort in working with patrons with disabilities. Issue 6 (9th March 2021) - Pionke, JJ
Abstract : Purpose: This article presents a secondary analysis of previously published data in order to drive discussion of the library profession's current state of preparedness in working with patrons with disabilities. Design/methodology/approach: This article used a secondary analysis of survey data that have been previously published to determine what the continuum of data said about the current state of preparedness in the profession when working with people with disabilities. Findings: A comparison of the data from both surveys reveals that there are not only gaps in library graduate school education related to disability and accessibility but also that those gaps are not being addressed through professional development and staff training after students enter the workforce. Research limitations/implications: This was a secondary analysis of data, so no new data could be added. There was also no representation from library graduate school administration. Practical implications: An awareness is built that there needs to be more instruction for library graduate students and library employees on topics related to disability, accessibility and assistive technologies. Originality/value: The topic has never been studied before in this kind of continuum of data, and the use of the secondary analysis of data with the library and information science profession is exceedingly rare.